The Role of Job Satisfaction in Mediating The Effect of Organizational Culture and Work Motivation on Employee Performance - Ni Made Nurperinayati (Global Researcher Network, 2021)
This study aims to analyze and explain the Role of Job Satisfaction in Mediating the Effect of Organizational Culture and Work Motivation on Employee Performance with research subjects of the Public Works Office and Spatial Planning of the Province of Bali. The research design used to answer this problem is quantitative with a sample size of 85 people calculated using the Slovin formula and determining the sample size using the probality sampling method. The data used in this study are primary and secondary data both quantitative and qualitative data. Data analysis used structural equation modeling (SEM) with the partial least square (PLS) method which obtained the following results: 1) Organizational culture has a positive and insignificant effect on employee performance at the Office of Public Works and Spatial Planning of Bali Province. 2) Work motivation has a positive and non-significant effect on employee performance at the Public Works Office and Spatial Planning of Bali Province. 3) Organizational culture has a positive and significant effect on employee job satisfaction at the Office of Public Works and Spatial Planning of Bali Province. 4) Work motivation has a positive and significant effect on employee job satisfaction at the Office of Public Works and Spatial Planning of Bali Province. 5) Job satisfaction has a positive and significant effect on employee performance at the Office of Public Works and Spatial Planning of Bali Province. 6) Job satisfaction is not a mediator of the influence of organizational culture on the performance of employees of the Public Works Office and Spatial Planning of the Province of Bali. 7) Job satisfaction is not a mediator of the effect of work motivation on the performance of employees of the Public Works Office and Spatial Planning of the Province of Bali.